Identification of a Costimulatory Molecule Gene Signature to Predict Survival and Immunotherapy Response in Head and Neck Squamous Cell Carcinoma - Aye, Ling; Song, Xiaole; Yang, Jingyi; Hu, Li; Sun, Xicai; Zhou, Jiaying; Liu, Quan; Yu, Hongmeng; Wang, Dehui (Frontiers in Cell and Developmental Biology, 2021)
Background: Head and neck squamous cell carcinoma (HNSCC) is one of the most common malignancies worldwide. Checkpoint blockade immunotherapy has made tremendous progress in the treatment of a variety of cancers in recent years. Costimulatory molecules constitute the foundation of cancer immunotherapies and are deemed to be promising targets for cancer treatment. This study attempted to evaluate the potential value of costimulatory molecule genes (CMGs) in HNSCC. Materials and Methods: Based on The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) dataset, we identified the prognostic value of CMGs in HNSCC. Subsequently, CMGs-based signature (CMS) to predict overall survival of HNSCC patients was established and validated. The differences of downstream pathways, clinical outcomes, immune cell infiltration, and predictive immunotherapy responses between different CMS subgroups were investigated via bioinformatic algorithms. We also explored the biological functions of TNFRSF12A, one risk factor of CMS, by in-vitro experiments. Results: Among CMGs, 22 genes were related to prognosis based on clinical survival time in HNSCC. Nine prognosis-related CMGs were selected to establish CMS. CMS was an independent risk factor and could indicate the survival of HNSCC patients, the component of tumor-infiltrating lymphocytes, and the immunotherapy response rate. Functional enrichment analysis confirmed that CMS might involve immune-relevant processes. Additionally, TNFRSF12A was related to poor prognosis and enhanced malignant phenotype of HNSCC. Conclusion: Collectively, CMS could accurately indicate prognosis, evaluate the tumor immune microenvironment, and predict possible immunotherapy outcomes for HNSCC patients.